2020
DOI: 10.1016/j.jjcc.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum lipoprotein (a) level on coronary plaque progression and cardiovascular events in statin-treated patients with acute coronary syndrome: a yokohama-acs substudy

Abstract: Background: Lipoprotein (a) [Lp(a)] has been reported to be a residual risk factor in patients who have achieved target lipid levels. The aim of the present study was to investigate the associations of Lp(a) with plaque progression and major cardiovascular events in patients with acute coronary syndromes (ACS). Methods: The Yokohama-ACS study included 102 patients with ACS who underwent intravascular ultrasound (IVUS) at baseline and at 10-month follow-up after percutaneous coronary intervention (PCI). The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…As for secondary prevention, the association between Lp(a) levels and the risk of subsequent CVEs has been recognized in the patients with established coronary artery diseases (CAD), even they were complicated with diabetes [6,7,19,23]. However, among studies that were targeted at subjects who had ever-experienced CVEs revealed inconsistent results [11–15,24]. As early as 2012, Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for secondary prevention, the association between Lp(a) levels and the risk of subsequent CVEs has been recognized in the patients with established coronary artery diseases (CAD), even they were complicated with diabetes [6,7,19,23]. However, among studies that were targeted at subjects who had ever-experienced CVEs revealed inconsistent results [11–15,24]. As early as 2012, Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy still exists in people who had previous CVEs, especially ACS [11][12][13]. Aside from the negative results, among studies that reported poor prognosis, there is also evidence to suggest differential predictive values of Lp(a) in individual components of RCVEs [7,12,[14][15][16][17]. Therefore, we conducted this study to further discuss the effects of Lp(a) on predicting RCVEs and components of it in patients with ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiologic studies of Lp(a) level in Japanese patients are limited, there are no anticipated ethnicity-related differences in olpasiran efficacy based on reports of similar plasma Lp(a) concentrations and distributions between Japanese and white populations, 22 as well as similarities in the increased prevalence of major adverse cardiovascular events due to an elevated Lp(a) level in patients with ASCVD. [23][24][25] The results from this single-dose study may also be extrapolated to support the development of olpasiran in other East Asian populations, such as Chinese and Korean patients.…”
Section: Discussionmentioning
confidence: 84%
“…Many previous studies have described the correlation between Lp(a) and coronary atherosclerosis progression using invasive imaging methods. In one study performed in 76 patients with acute coronary syndrome (ACS) who underwent intravascular ultrasound(IVUS) at baseline and at 10‐month follow‐up after percutaneous coronary intervention, the results showed that patients with serum levels of Lp(a) >20 mg/dl had slight plaque progression despite of statin therapy, suggesting Lp(a) levels could be an alternative predictor of further plaque progression 10 . Similarly, Hartmann et al reported that Lp(a) was positively related to plaque progression in the left main coronary artery by serial IVUS examinations 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between Lp(a) and coronary atherosclerosis progression remains controversial. Previously, two study groups assessed the predictive utility of Lp(a) in coronary atherosclerosis progression by intravascular ultrasound, opposite results were obtained 9,10 . With the development of computed tomography technology, coronary computed tomography angiography (CTA) has been widely used for non‐invasive assessment of coronary atherosclerosis at outpatient department.…”
Section: Introductionmentioning
confidence: 99%